Equity, Social Justice, and English Medium Instruction Case Studies from Asia - Giri, Ram Ashish; Padwad, Amol; Kabir, Mian Md. Naushaad (Springer Nature Singapore : Imprint: Springer, 2024)
XX, 414 p. 35 illus., 3 illus. in color.